EINFORCING ACTION LEARNING WITII KNOWLEDGE CREATION IN-ORDER-TO IMPROVE PEDAGOGICAL CONTENT KNOWLEDGE AMONG SCHOOL TEACHERS - Alimuddin, Zulfikar
As the knowledge workers in schools, teachers are required to improve their teaching competence continuously. The author argued that by focusing on Pedagogical Content Knowledge (PCK), teachers should be able to regulate teaching and learning dynamics in class so that students could improve their learning, the primary indicator of the schools' performance. Pedagogical Content Knowledge is a form of teaching knowledge created from combining at least content knowledge and pedagogical knowledge. Having PCK means a teacher can teach most effectively by matching the content knowledge they are teaching and the way to teach it in various classrooms and student conditions. Considering that many conventional and usual teacher professional development has found problems in improving teachers' competence, the author argued that teachers should be facilitated with a framework that could help teachers be autonomous and long-life learners. Those qualities' essential aspect requires teachers to learn from mistakes, reflect, and share knowledge among professionals. Supported by transformative learning theory and constructivist learning theory, the author argued that improving teachers' PCK requires a particular framework that reinforces individual learning with organizational learning. This study investigates the suitability of reinforcing Action Learning with Knowledge Creation to improve teachers' PCK. To investigate it, the author devised learning instruments and an assessment instrument based on Watkins and Marsick Continuous Learning Model and SECI with PCK as the context for the learning instruments. This study is quasi-experimental with a pretest-post-test design. The data was collected by examining and scoring teachers' answers to the assessment instrument using the instruments' scoring rubric. The scoring rubric use a Likert-scale like scoring system. Three raters were assigned to rate teachers' answers, and the agreement between raters was reached by adapting the Delphi technique. The collected data were analyzed using the ANCOVA test and t-test. The result shows that Action Learning and Knowledge Creation could improve teachers' PCK separately. However, the test result also indicates that the treatment that reinforces action learning with knowledge creation does not significantly differ compared to action learning ouly treatment and knowledge creation only treatment.